2017
DOI: 10.2214/ajr.17.17938
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Cortical Thickening and Bone Heterogeneity of the Subtrochanteric Femur Measured With Quantitative CT as Indicators for Early Detection of Atypical Femoral Fractures in Long-Term Bisphosphonate Users

Abstract: Long-term BP users with a subsequent AFF had a thicker lateral cortex and higher lateral cortex BMD at the subtrochanteric area before the fracture on QCT than BP users who did not sustain a femoral fracture and BP-naïve patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In cases with normal radiographs on the contralateral side, but where there is still clinical suspicion, computed tomography (CT) should be considered, since fracture lines, not visible on radiographs, might be diagnosed. Lee et al 36 have shown that patients with a subsequent AFF have a thicker lateral cortex in the subtrochanteric region of the femur on CT before the fracture event, than bisphosphonate (BP) users who did not sustain a femoral fracture, and than BP-naïve patients. Thus, CT might be used for the early detection of AFF in long-term BP users.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In cases with normal radiographs on the contralateral side, but where there is still clinical suspicion, computed tomography (CT) should be considered, since fracture lines, not visible on radiographs, might be diagnosed. Lee et al 36 have shown that patients with a subsequent AFF have a thicker lateral cortex in the subtrochanteric region of the femur on CT before the fracture event, than bisphosphonate (BP) users who did not sustain a femoral fracture, and than BP-naïve patients. Thus, CT might be used for the early detection of AFF in long-term BP users.…”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…Quantitative CT analyses are able to show that long-term users of bisphosphonates with a subsequent fracture have a thicker subtrochanteric lateral cortex with a higher bone mineral density compared with patients who did not sustain a femoral fracture. 36 This is associated with a higher lateral femoral bowing angle with a vertex located at the site of the later subtrochanteric fracture. 37 …”
Section: Evaluation and Diagnosismentioning
confidence: 99%
“…It is "atypical" because osteoporotic fractures rarely involve the lateral femoral cortex. Due to poor healing potential and risk for fracture completion, patients may undergo prophylactic surgical fixation [24].…”
Section: Atypical Femoral Fracturementioning
confidence: 99%
“…Bilateral femoral radiographs may demonstrate asymptomatic contralateral fracture requiring prophylactic fixation. When radiographs are negative, CT and MR improve fracture detection in symptomatic patients on bisphosphonate therapy [23,24]. Similar to other tensile-sided stress fractures, healing is delayed [22].…”
Section: Atypical Femoral Fracturementioning
confidence: 99%
“…A "beaking" or "flaring" phenomenon of localized periosteal or endosteal thickening of the lateral cortex often precedes an AFF, and this may aid in early detection. 29 Standard imaging modalities such as magnetic resonance imaging or computed tomography can visualize beaking, bone heterogeneity, the fracture line, and associated bone marrow edema. 10 Although less specific, radionuclide bone scans may detect hyperemia suggestive of AFF.…”
Section: Definition and Diagnosismentioning
confidence: 99%